A lethal effect associated with polymorphism of the NOR-bearing chromosomes in rainbow trout (Oncorhynchus mykiss) - Porto-Foresti, Fábio [UNESP]; Oliveira, Claudio [UNESP]; Gomes, Eduardo A. [UNESP]; Tabata, Yara A.; Rigolino, Marcos G.; Foresti, Fausto [UNESP] (Sociedade Brasileira de Genética, 2004)
Cytogenetic analysis of a rainbow trout stock showed that the nucleolar organizing regions were located subterminally on the long arm of a submetacentric chromosome pair and occurred as a single chromosomal segment (phenotype N1) or as two chromosomal segments separated by a short euchromatic segment (phenotype N2). Cytogenetic analysis also showed that there were N1N1 and N1N2 individuals but no N2N2 individuals. Analysis of the different includedphenotypes incluted that the population was not in Hardy-Weinberg equilibrium (chi² = 19.333; p < 0.01), and that a higher frequency of individuals had the N1N2 phenotype. Experimental crosses involving four males (two N1N1 and two N1N2) and four females (one N1N1 and three N1N2) yielded eight broods. There were no significant differences between the expected and observed frequencies of offspring resulting from crosses involving N1N1 x N1N2 individuals. However, significant differences were seen in crosses involving N1N2 x N1N2 parents because of the a high incidence of N1N2 fishes and the absense of N2N2. The lack of N2N2 individuals in the parental sample and their absence among the offspring of the experimental crosses suggested that this genetic combination may be lethal in rainbow trout. The survival rates of embryonic eyed egg and fry stage individuals were not different, indicating that the possible lethal effect may occur during more advanced ontogenetic phases.
Keywords: NOR polymorphism; paracentric inversion; fish cytogenetics; rainbow trout